Discourse Reference Is Bimodal: How Information Status in Speech Interacts with Presence and Viewpoint of Gestures. Issue 1 (2nd January 2019) - Debreslioska, Sandra; Gullberg, Marianne
ABSTRACT: Speakers use speech and gestures to represent referents in discourse. Depending on referents' information status, in speech speakers will vary richness of expression (e.g., lexical noun phrase [NP]/pronoun), nominal definiteness (indefinite/definite), and grammatical role (subject/object). This study tested whether these three linguistic markers of information status interact with presence of gestures and gestural viewpoint (observer/character). The results show that gestures are more frequent with less accessible referents expressed with richer spoken forms but that richness of expression does not interact with viewpoint. In contrast, nominal definiteness and grammatical role interact with both presence and viewpoint of gestures. Gestures occur mainly with indefinite lexical NPs and objects. Character viewpoint gestures occur mainly with indefinite lexical NPs and objects plus predicates. The results shed light on when and how speakers use gestures in connected discourse and specifically highlight the discursive function of gestural viewpoint.